Perceptions of Program Abuse and Support for Social Insurance. Issue 1 (January 2021) - Bokemper, Scott E.; Fang, Albert H.; Huber, Gregory A.
Do perceptions of abuse in social insurance programs undercut program support? Answering this causal question is difficult because perceptions of program abuse can arise from multiple potential causes. Examining the case of disability insurance, we circumvent this challenges using laboratory experiments to study the interplay between program abuse and program support. Specifically, we test whether participants vote to reduce benefit levels when they observe program abuse, even if that abuse is not directly costly to them. We use a labor market shock to induce program abuse and show that the observation of a healthy worker receiving benefits causes workers who are unaffected by the shock to vote to lower benefits. This effect arises only when reducing benefit levels also reduces taxes. Our results demonstrate a causal link between program abuse and diminished support for social insurance, validating accounts that stress how violations of cooperative norms can undercut socially beneficial government programs.